Maxillary molar distalization with the indirect Palatal miniscrew for Anchorage and Distalization Appliance (iPANDA). - Eduardo Yugo Suzuki (2018)
Distalization of the maxillary molars is an important treatment option for the correction of Class II malocclusions. The purposes of this study were to introduce the clinical application of the indirect Palatal miniscrew Anchorage and Distalization Appliance (iPanda) and to describe the dental and skeletal effects obtained with this innovative appliance. Pretreatment (TO), post-distalization (T1), and posttreatment (T2) lateral cephalometric radiographs and dental casts of 20 consecutively treated adult patients (mean age 23.2 ± 4.7 years) with Class II molar relationship were analyzed. All patients were treated with the iPanda for maxillary molar distalization. The iPanda was anchored on a pair of midpalatal miniscrew implants to deliver the distalizing force to the maxillary first molars. The iPanda was the only appliance used during the distalization phase of treatment. A paired t test analysis was used to statistically assess the effects of treatment. A Class I molar relationship was obtained in a mean period of 3.2 ± 0.6 months. Cephalometric analysis demonstrated that the maxillary first molars were significantly distalized by an average 4.5 ± 1.5 mm (P < .001) and were intruded by a mean of 1.0 mm ± 0.8 mm (P < .05). No significant change in the inclination of the first molars was observed. No significant change in the mandibular plane was observed. Dental model analysis demonstrated an asymmetric pattern of distalization between right (4.5 ± 2.2 mm) and left (3.1 ± 2.1 mm) first molars. The transverse width of the dental arch was maintained. No significant rotation of the first molars was observed. This study demonstrated that the innovative iPanda is effective to bodily distalize the maxillary molars into a Class I molar relationship and to provide maximum anchorage.